Singing Synthesizers: Musical Language Revitalization through UTAUloid - Sleeper, Morgan (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée, 2024)
Music plays many important roles in language revitalization, from attracting learners and fostering speech communities to supporting language learning. These effects, however, are largely independent from the skills which linguists bring to language revitalization. This study introduces one concrete way in which applied linguistics can directly support musical language revitalization with UTAUloids – speech-and-music software synthesizers – illustrated through the creation of a Cherokee UTAUloid as part of ancestral language reclamation by a learner-linguist Cherokee Nation citizen. Through their focus on “massive collaboration,” low-resource music production, and youth involvement, UTAUloids are uniquely situated to serve as instruments for language revitalization. Even the act of creating an UTAUloid itself allows speakers and learners who may not consider themselves “musical” to contribute to musical language revitalization, and this study provides a step-by-step methodology to make creating an UTAUloid as accessible as possible for anyone interested in incorporating music into their own language revitalization practice.